A Survey Analysis Of Community Water Fulfillment For Spam Patimban, Subang Regency, Indonesia - Assegaf, Milla Marlina; Sriharyati, Santy Sriharyati; Rengganawati, Hana Rengganawati (Program Studi Administrasi Bisnis, 2024)
To achieve the target of 100% coverage of drinking water, it is necessary to improve services and investment as a whole. The problem faced in the provision of drinking water today is the low coverage of services because many residents have not utilized services from the government, both tap water PDAM and PAMSIMAS. Even a small portion of the population still uses shallow groundwater/shallow wells and rainwater as an alternative. Survey activities were conducted in 950 respondents spread across 5 (five) sub-districts in 40 villages, namely Compreng Sub-District (8 villages), Cipunagara Sub-District (10 villages), Sukasari District (7 villages), Pusakanagara Sub-District (8 villages) and Pusakanagara Sub-District (7 villages).